2019
DOI: 10.1101/gr.245456.118
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive and dynamic transcription initiation in Saccharomyces cerevisiae

Abstract: Transcription initiation is finely regulated to ensure proper expression and function of genes. The regulated transcription initiation in response to various environmental stimuli in a classic model organism Saccharomyces cerevisiae has not been systematically investigated. In this study, we generated quantitative maps of transcription start sites (TSSs) at a single-nucleotide resolution for S. cerevisiae grown in nine different conditions using no-amplification nontagging Cap analysis of gene expression (nAnT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 98 publications
(125 reference statements)
7
72
1
Order By: Relevance
“…We believe therefore that increased chromatin mobility upon serum starvation correlates with PIC breakdown. Conversely, when serum is present in the medium, activity of RNA Pol II and of PIC enzymes is restored and PIC will assemble onto DNA, both pervasively across the genome at background levels (pervasive transcription) and more stably at genes [53,54]. Reduced mobility of chromatin in the presence of serum suggests that stable PIC binding may serve as an anchoring function for individual chromatin fibers, on top of its essential function in transcription initiation.…”
Section: Discussionmentioning
confidence: 99%
“…We believe therefore that increased chromatin mobility upon serum starvation correlates with PIC breakdown. Conversely, when serum is present in the medium, activity of RNA Pol II and of PIC enzymes is restored and PIC will assemble onto DNA, both pervasively across the genome at background levels (pervasive transcription) and more stably at genes [53,54]. Reduced mobility of chromatin in the presence of serum suggests that stable PIC binding may serve as an anchoring function for individual chromatin fibers, on top of its essential function in transcription initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, these numbers are very similar to the estimated occurrence of AP in humans, despite the vast differences in their genomes. The authors found that as many as 85% of the genes possessing multiple promoters exhibited significant shifts of promoter activity in at least one of the nine tested conditions (Lu & Lin, 2019). Such a condition-dependent use of APs indicates that it might support differential gene expression, providing an additional layer of regulation (Ayoubi & Van De Yen, 1996).…”
Section: Alternative Promotersmentioning
confidence: 96%
“…Interestingly, this number is dramatically elevated following energy stress, suggesting condition-specific regulation (Tamarkin-Ben-Harush et al, 2017). A recently published work employed an improved CAGE technique to map, at the nucleotide resolution, hundreds of thousands of TSSs in the yeast Saccharomyces cerevisiae (Lu & Lin, 2019). The authors found that 56% of the expressed protein-coding genes employ alternative promoters when exposed to changing environmental conditions.…”
Section: Alternative Promotersmentioning
confidence: 99%
“…The development of high resolution 5 0 end-centered expression profiling techniques, such as oligo-capping methods 18 or cap analysis of gene expression (CAGE) 19 , has greatly advanced our understanding of gene regulation at a transcription initiation level. Studies employing these techniques have revealed both common and distinct features of the core promoters and their origin and regulation, in many organisms [20][21][22] . In mammals, for example, CAGE sequencing (CAGE-seq) analyses revealed that a large fraction of cell-type specific transcripts in stem and cancer cells originate from long terminal repeats (LTRs) of retroelements 23,24 .…”
mentioning
confidence: 99%